2019
DOI: 10.1515/jcim-2019-0133
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of Terminalia bellerica Roxb. and gallic acid in experimentally induced diabetic animals

Abstract: AbstractBackgroundDiabetic wound are the major problem of society because of its delay healing of wound in hyperglycemia patient. The target of this study need to know the gallic acid compelling synergistically wound healing in diabetic animals as it is available in fruit extract or is more effective in given pure form in diabetic animals. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Rocasalbas [62] 2013 Gelatin hydrogel X Díaz-González [63] 2012 X Bektas N [64] 2020 Hydrogel X X Chitosan + gallic acid Thi [31] 2020 Gelatin hydrogel X X Singh [65] 2019 X Yang [66] 2016 X Stefanov [30] 2016 X X (ExV)…”
Section: Chitosan + Plan Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rocasalbas [62] 2013 Gelatin hydrogel X Díaz-González [63] 2012 X Bektas N [64] 2020 Hydrogel X X Chitosan + gallic acid Thi [31] 2020 Gelatin hydrogel X X Singh [65] 2019 X Yang [66] 2016 X Stefanov [30] 2016 X X (ExV)…”
Section: Chitosan + Plan Extractsmentioning
confidence: 99%
“…The group treated with gallic acid effectively showed improved re-epithelialization and wound remodeling compared to the other groups. Researchers believe that this injectable ROS-scavenging hydrogel has great potential for wound treatment and tissue regeneration, where oxidative damage by ROS contributes to the pathogenesis In another study, Singh et al [65] investigated the wound healing activity of the Terminalia bellerica fruit ethanolic extract compared with its active constituent, gallic acid, in experimentally induced diabetic animals. Rats were divided into seven groups: group I normal control (saline 5 mL/Kg), group II normal experimental (Terminalia bellerica extract 400 mg/Kg), group III normal experimental (gallic acid 200 mg/Kg), group IV diabetic control (vehicle only 5 mL/Kg), group V diabetic experimental (Terminalia bellerica extract 400 mg/Kg), group VI diabetic experimental (gallic acid 200 mg/Kg), group VII diabetic standard (Vitamin C 200 mg/Kg).…”
Section: Chitosan and Gallic Acidmentioning
confidence: 99%
“…GA has antioxidant, antiinflammatory, and analgesic effects (Comino-Sanz et al, 2021). Studies have shown that GA can improve wound healing in diabetic rats, and promote neovascularization, and collagen deposition during wound healing in diabetic animals (Singh et al, 2019). In vitro studies have shown that GA upregulates the expression of antioxidant genes, stimulates cell migration on fibroblasts, and activates healing factors (Yang et al, 2016).…”
Section: Gallic Acidmentioning
confidence: 99%
“…In general, Ginsenosides Rb1 (Zhang et al, 2021), Lupeol (Pereira Beserra et al, 2020), garlic acid (Singh et al, 2019), Ferulic acid (Dwivedi et al, 2022), Hesperdin (Jagetia and Rao, 2022), Aloin (Liu et al, 2015), Simmondsia cheinensis (Ranzato et al, 2011), Snail mucins (Gugliandolo et al, 2021), Angelica Sinensis ethanol extract (Bai et al, 2012b), Apigenin (Choi et al, 2016)have important potential to promote wound healing, and the molecular mechanism should be further studied. This conclusion is supported by desirable results, both in animal and cell experiments.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The group treated with gallic acid effectively showed improved re-epithelialization and wound remodeling compared to the other groups. Researchers believe that this injectable ROS-scavenging hydrogel has great potential for wound treatment and tissue regeneration, where oxidative damage by ROS contributes to the pathogenesis In another study, Singh et al [61] investigated the wound healing activity of the Terminalia bellerica fruit ethanolic extract compared with its active constituent, gallic acid, in experimentally induced diabetic animals. Rats were divided into seven groups: group I normal control (saline 5 mL/Kg), group II normal experimental (Terminalia bellerica extract 400 mg/Kg), group III normal experimental (gallic acid 200 mg/Kg), group IV diabetic control (vehicle only 5 mL/Kg), group V diabetic experimental (Terminalia bellerica extract 400 mg/Kg), group VI diabetic experimental (gallic acid 200 mg/Kg), group VII diabetic standard (Vitamin C 200 mg/Kg).…”
Section: Chitosan and Gallic Acidmentioning
confidence: 99%